Development of E-learning Based Mechatronics Learning Module for Distance Education - Maulana, Muhamad Riyan (Yayasan Insan Mulia Bima, 2024)
In the growing context of distance education, e-learning modules for mechatronics offer great potential to increase learning flexibility and effectiveness, but face challenges related to concept understanding, student motivation, and technical constraints. This study aims to evaluate the effectiveness of mechatronics-based e-learning modules in improving students' understanding of mechatronics concepts and to identify challenges and areas of improvement needed. Using a qualitative approach, the study involved in-depth interviews with 20 students over a four-month period as well as focus group discussions and document analysis. The data obtained was analysed thematically to reveal students' views and experiences. The findings show that e-learning modules that integrate multimedia elements such as animations and interactive simulations significantly improve students' understanding and motivate them through interactive elements. However, technical constraints such as unstable internet connection and device compatibility issues, as well as the need for additional support in self-directed learning, hindered the learning experience. Student feedback indicated the need for improvements to the module navigation and user guide. In conclusion, the e-learning module was effective in improving student understanding and motivation, but requires technical improvements and additional support to optimise its benefits in distance education.